Social and Physical Planning for the Elimination of Urban Poverty - Herbert J. Gans (Washington University Law Quarterly, 1963)
The provision of public facilities is also a traditional planning emphasis, dating back to the days when the planner was an ally of the reformers who were fighting for the establishment of these facilities. Out of this has come the belief that public facilities are crucial agencies in people's lives, that up-to-date facilities and programs will encourage intensive use of them and that this in turn will help significantly in achieving the aims of guided mobility planning. Despite the intensity of the planner's belief in neighborhood and public facility use, there is no evidence that these two planning concepts are as important to low income people as they are to planners. Consequently, it is fair to ask whether such concepts are as crucial to the elimination of urban poverty and deprivation as is signified by their appearance in some guided mobility plans. The answer to this question requires a brief discussion of the nature of contemporary urban poverty.